OPTIMIZING DIGITAL ADMINISTRATION INNOVATION: THE STRATEGIC ROLE OF BUSINESS DATA ANALYTICS AND ARTIFICIAL INTELLIGENCE (POLITEKNIK LP3I JAKARTA, 2026)
This study examines the Optimization of Digital Administration Innovation, the Strategic Role of Business Data Analytics and Artificial Intelligence aims to identify effective strategies in integrating data and artificial intelligence in digital administration processes and to improve operational efficiency, support decision-making, explore the impact of artificial intelligence with best practice models, analyze challenges, barriers, ethics, privacy and data security as well as sustainable innovation. This study employs a qualitative descriptive approach to provide detailed descriptions of the experiences and perceptions of employees and managers in several business and public organizations in Jakarta that have implemented data analytics and artificial intelligence in their digital operations. The data collection techniques employed include interviews, observation, and document analysis methods. The sample consists of participants with relevant experience in using business data analytics and artificial intelligence in digital administration, with approximately 15 participants representing the organization. The analysis employed thematic analysis and data triangulation. The results of the study indicate that business organizations can conduct effective strategic analysis to integrate data and artificial intelligence in digital administration processes. Enhance operational efficiency by leveraging digital innovation to reduce time and costs. Support decision-making by providing knowledge of how to analyze the correct data for decision-making. Explore the impact of artificial intelligence by examining its applications in process and quality improvement. Help organizations implement digital innovation effectively and sustainably. Identifying challenges and barriers to adopting digital technologies, encouraging stakeholder engagement and contribution, and guiding ethics, privacy, and data security.